Basal autophagy protects cardiomyocytes from doxorubicin-induced toxicity. (31st August 2016) - Pizarro, Marcela; Troncoso, Rodrigo; Martínez, Gonzalo J.; Chiong, Mario; Castro, Pablo F.; Lavandero, Sergio
Abstract: Doxorubicin (Doxo) is one of the most effective anti-neoplastic agents but its cardiotoxicity has been an important clinical limitation. The major mechanism of Doxo-induced cardiotoxicity is associated to its oxidative capacity. However, other processes are also involved with significant consequences for the cardiomyocyte. In recent years, a number of studies have investigated the role of autophagy on Doxo-induced cardiotoxicity but to date it is not clear how Doxo alters that process and its consequence on cardiomyocytes viability. Here we investigated the effect of Doxo 1 uM for 24 h of stimulation on cultured neonatal rat cardiomyocytes. We showed that Doxo inhibits basal autophagy. This inhibition is due to both Akt/mTOR signaling pathway activation and Beclin 1 level decrease. To assess the role of autophagy on Doxo-induced cardiomyocyte death, we evaluated the effects 3‐methyladenine (3-MA), bafilomycin A1 (BafA), siRNA Beclin 1 (siBeclin 1) and rapamycin (Rapa) on cell viability. Inhibition of autophagy with 3-MA, BafA and siBeclin 1 increased lactate dehydrogenase (LDH) release but, when autophagy was induced by Rapa, Doxo‐induced cardiomyocyte death was decreased. These results suggest that Doxo inhibits basal autophagy and contributes to cardiomyocyte death. Activation of autophagy could be used as a strategy to protect the heart against Doxo toxicity.